GNL3 Regulates SIRT1 Transcription and Promotes Hepatocellular Carcinoma Stem Cell-Like Features and Metastasis. (7th April 2022) - Zhang, Songyan; Zhao, Haoran; Chen, Yang; Zhang, Yubao
Abstract : The expression of GNL3 in hepatocellular carcinoma was detected, and its effect on the proliferation and metastasis of hepatocellular carcinoma cells was investigated. Hepatocellular carcinoma and adjacent tissues were collected. The mRNA and protein expression levels of GNL3 were detected by qRT-PCR, Western blot, and immunohistochemistry. The relationship between GNL3 and the prognosis of liver cancer was analysed using public databases. A GNL3 interfering plasmid was constructed, and the effects of GNL3 on the proliferation of HepG2 and PLC-PRF-5 hepatoma cells were detected by the CCK-8 method. Transwell chamber assays were used to detect the effects of GNL3 on the migration and invasion of hepatocellular carcinoma cells. The effects of GNL3 on SIRT1 expression and stem cell markers were analysed. The effect of GNL3 on the proliferation of hepatocellular carcinoma was detected in a subcutaneous tumor-bearing animal model. The results showed that the mRNA and protein levels of GNL3 were higher than those of adjacent tissues. The overall survival (OS) of HCC patients with high GNL3 expression was worse. In vivo and in vitro experiments confirmed that silencing GNL3 could inhibit the proliferation, migration, and invasion of hepatocellular carcinoma cells. Mechanistic studies have shown that GNL3 regulates SIRT1 expression. GNL3 mediates the stem cell-like properties of HCC cells through SIRT1. In conclusion, this study found that GNL3 increased expression in hepatocellular carcinoma, which promoted the malignant biological behavior of hepatocellular carcinoma cells and was related to the cell dry phenotype. This study has certain significance in evaluating the prognosis of HCC patients.